Use of Self-Management Strategies in New Students of Public Health Sciences State University of Malang - Tiarani Dania Uly, Adinda; Putri Kurniawati, Amalia; Rahayu, Erni Dwi; Mahardika, Grace Widya Dharma (Tarqabin Nusantara Group, 2024)
The transition period from student to student is a challenge in itself for new students. These changes require the right strategy to speed up the adaptation process to the new environment. To be able to organize yourself well, self-management is needed. Self-management is a process where a person directs changes in his or her behavior using one or a combination of several strategies. This research aims to find out how self-management affects new students majoring in Public Health at, the State University of Malang. The research method used is quantitative using direct socialization. The instrument used in this research was counseling material. The data collection process is through pretest-posttest with a multiple choice test with a total of 10 questions. The data that has been collected is then subjected to descriptive analysis and presented in narrative form. The research results showed that the level of student knowledge before the socialization was carried out was relatively low with an average of 50/100. Then after socialization was carried out, the average increased to 83/100. From this increase in results, it can be concluded that students already understand self-management and are expected to be able to apply it.